Clinical Profile of Pediatric Patients with Acyanotic Congenital Heart Disease in Dr. Soetomo General Hospital Surabaya - Kartika Hardiyani; Taufiq Hidayat; Alit Utamayasa; Mahrus Abdur Rahman; Teddy Ontoseno (Indian Journal of Forensic Medicine & Toxicology, 2021)
Congenital Heart Diseases (CHD) are classified as Acyanotic or Cyanotic CHD. Prevalence of CHDaccording to various studies is 8-10 per 1000 live births worldwide, 10% of cases became infant mortalityin developing countries. This research aims to study the characteristics and clinical presentations in childrenwith acyanotic CHD in Dr. Soetomo General Hospital. A retrospective observational study from children withacyanotic type of CHD from medical record outpatient clinic in the Division of Neonatology and PediatricWard at Dr. Soetomo General Hospital from June to December 2016. Age, sex, heart defect, comorbid andnutritional status were taken from the medical record. The most dominant clinical profile was female witha mean age of 4 years. Atrial Septal Defect was the most common type of left-to-right shunt, followed byVentricular Septal Defect, and Patent Ductus Arteriosus. Pulmonary Stenosis was the most common typeof obstructive lesion, followed by Aortic Stenosis. Complications of acyanotic CHD were dominated byrecurrent respiratory tract infections followed by growth and developmental disorder, and heart failure. Themost common nutritional status was moderate malnutrition.